Chlamydia trachomatis Tarp Harbors Distinct G and F Actin Binding Domains That Bundle Actin Filaments - Jiwani, Shahanawaz (American Society for Microbiology, 2013)
All species of Chlamydia undergo a unique developmental cycle that transitions between extracellular and intracellular environments and requires the capacity to invade new cells for dissemination. A chlamydial protein called Tarp has been shown to nucleate actin in vitro and is implicated in bacterial entry into human cells. Colocalization studies of ectopically expressed enhanced green fluorescent protein (EGFP)-Tarp indicate that actin filament recruitment is restricted to the C-terminal half of the effector protein. Actin filaments are presumably associated with Tarp via an actin binding alpha helix that is also required for actin nucleation in vitro, but this has not been investigated. Tarp orthologs from C. pneumoniae, C. muridarum, and C. caviae harbor between 1 and 4 actin binding domains located in the C-terminal half of the protein, but C. trachomatis serovar L2 has only one characterized domain. In this work, we examined the effects of domain-specific mutations on actin filament colocalization with EGFP-Tarp. We now demonstrate that actin filament colocalization with Tarp is dependent on two novel F-actin binding domains that endow the Tarp effector with actin-bundling activity. Furthermore, Tarp-mediated actin bundling did not require actin nucleation, as the ability to bundle actin filaments was observed in mutant Tarp proteins deficient in actin nucleation. These data shed molecular insight on the complex cytoskeletal rearrangements required for C. trachomatis entry into host cells.